MORPHOLOGICAL VARIABILITY OF THE TOPMOUTH GUDGEON PSEUDORASBORA PARVA (Temminck et Schlegel, 1846) IN THE RESERVOIRS OF THE BALKHASH BASIN (Experimental biology, 2022)
Thetopmouth gudgeonPseudorasboraparvaTemminck et Schlegel, 1846, has become one of the most common alien fish on the Eurasian continent [1]. The natural distribution area of the species is the inland waters of Japan, Taiwan, Hainan, China and Korea. Currently, the Amur chebachok has spread widely across the reservoirs of Eurasia as a result of the introduction of herbivorous fish from the reservoirs of the People's Republic of China.According to a number of authors, the Amur chebachok appeared in the reservoirs of Kazakhstan in 1958, when larvae of white amur and white carp were brought from the Sungari River (China, Amur River basin) to the Almaty pond farm [2-4]. From ponds, this species spread in the Ile River system, and after the 1960s it expanded its habitat by settling widely in the water system of the Balkash basin. According to G. M. Dukravets, Amur chebachok is quite likely in all basins where carp and white amur planting material was imported.The Balkash basin, according to A.F. Karpevich's definition, was a gigantic biological vacuum that could easily be filled with any biological species capable of surviving in its abiotic conditions. After large-scale acclimatization works, the native ichthyofauna of the Balkash basin was exposed to various impacts due to the formation of new biocenoses in the basin. To date, the species diversity of the ichthyofauna of the Balkash basin is characterized by an abundance of acclimatizing species that have displaced native fish species by invasion and self-settlement.
Keywords: Amur chebachok, acclimatization, invasion, alien species, Balkash basin, small reservoirs, Ile River.; Thetopmouth gudgeon PseudorasboraparvaTemminck et Schlegel, 1846